Analysis of blood gases, serum fat and serum protein: a new approach to estimate survival chances of stranded Harbor seal (Phoca vitulina) pups from the German North Sea - Witte, Katharina A; Driver, Jörg; Rosenberger, Tanja; Adler, Sven; Siebert, Ursula (BioMed Central Ltd., 2014)
Abstract Background Facing numerous challenges, such as illness, storms or human disturbance, some harbor seal ( Phoca vitulina ) pups lose contact to their dams and are found abandoned along the North Sea coast. In Schleswig-Holstein, pups with the prospect of surviving rehabilitation are admitted to the Seal Center Friedrichskoog. Despite elaborate clinical health assessments on admission, including differential hematology, in 2010, 17% of 108 admitted pups did not survive the first 20 days. The death rate during the years 2006 and 2009 varied between 9 and 19%. To broaden the spectrum of variables which could be predictive for survival, blood gas and serum analyses were performed for 99 pups using venous blood. Variables included total CO 2 , pH, partial CO 2 , HCO 3 – , base excess and anion gap as well as glucose, urea nitrogen, sodium, potassium and chloride. Moreover, total serum protein and fat (triglyceride) concentrations were measured for all pups on admission. Results Repeated measurements of 12 randomly selected individuals revealed a significant (p = 0.002) positive influence of time in rehabilitation on triglyceride concentrations. This trend probably shows the improvement of the pups’ nutritional status as a consequence of the shift from milk replacer formula to fish. No such positive influence was detected for total protein concentrations though. Hematologic values, including blood gases, were not predictive for survival. Conclusions For the first time blood gas values are reported in this study for a large sample size (N = 99) of seal pups (regardless of their health status). The ranges and medians calculated from the data can serve as a stepping stone towards the establishment of reference values for neonate harbor seals. However, future investigations on the development of blood gases in harbor seals with different health conditions and ages over time are necessary to allow for a better understanding of acid–base regulation in harbor seals.